Prostate Cancer Pathology, Screening, and Epidemiology - Crawford, E. David (MedReviews, LLC, 2001)
Recent advances in the understanding of prostate cancer pathology, screening methods, and epidemiology were discussed at the 11th International Prostate Cancer Update. Regarding pathology, Dr. Gary Miller enumerated several factors that lead to the perception of prostate cancer as “unpredictable.” These include the disease’s multifocal nature, variable progression rates, and the uncertainty regarding the point at which carcinomas metastasize. Screening methods have been the subject of research by the Laval University Prostate Cancer Screening Program since 1988. Dr. Fernand Labrie presented the results of this 10-year study. Dr. Daisaku Hirano presented data from his studies of prostate cancer epidemiology in Japan as compared to the United States. The role of environmental factors, particularly diet, in prostate cancer pathogenesis and development is supported by the increase of the disease in Japan, concurrent with the “westernization” of diet there. Finally, useful information was presented on new computer- and Internet-based diagnostic and research tools.